Aminoglycoside utilization in elderly inpatients: Implications for renal health and adverse outcomes - Yu-Hsin Wu, MD; Yu-ying Wu, MD; Hsi-Hao Wang, MD, MPH; I-Fan Lin, MD (Archives of Gerontology and Geriatrics Plus)
Background: Aminoglycosides, maintaining antimicrobial efficacy, are considered for combating multidrug-resistant pathogens. Their contemporary use, combined with vigilant preventive strategies, may not universally lead to lasting renal complications in elderly inpatients. Methods: This study examined data from the National Health Insurance Registry Database, focusing on elderly inpatients (aged 60 and above) hospitalized between 2000 and 2017 due to pneumonia, urinary tract infections, or bacteremia. Patients treated with aminoglycosides were compared to those receiving other antibiotics. Patient follow-up continued until the occurrence of renal disease, death, or for three months post-discharge, based on diagnoses coded in the International Classification of Diseases. Results: Among 938,052 elderly inpatients admitted for infections, 29.19 % were prescribed aminoglycosides. Patients receiving aminoglycosides tended to be younger and had fewer associated health conditions compared to those treated with other antibiotics. The overall incidence of renal disease was 2.03 % during hospitalization and it increased to 17.45 % at the three-month follow-up. While no increased risk for renal disease was observed in the aminoglycoside group compared to other antibiotics, it correlated with higher rates of death and intensive care unit transfer. Specific comorbidities, such as diabetes mellitus, heart failure, and liver disease, exhibited a stronger association with the development of renal disease compared to aminoglycosides. Conclusion: Current aminoglycoside use did not contribute to a higher incidence of lasting renal disease compared to other antibiotics but was linked to increased morbidity and mortality. Caution is crucial when administering aminoglycosides to elderly patients to prevent adverse outcomes.